Physical and emotional development of adolescents with low motor competence: Mothers' perspectives. (June 2022) - Timler, Amanda; Bulsara, Caroline; Hands, Beth
Background: Parent support influences adolescent's social-emotional well-being. One factor that may influence parent's perception of support is their child's level of motor competence. Aim: The purpose of this study was to explore mothers' experience of providing support for the health of adolescents with low motor competence physical and emotional development. Methods: A phenomenological approach was used to guide this study. After initial screening, five one-on-one interviews with mothers of adolescents aged 12–16 years were conducted. Results: Analysis of the interviews identified five themes of 'supportive building blocks', 'building achievement and commitment, ' 'building mechanisms for future support' 'building stability in relationships' and 'building confidence and a sense of autonomy'. Mother's awareness of their child's motor difficulties resulted in their active provision of alternative strategies for their child by building self-confidence and seeking support from health professionals. Conclusion: Mothers were aware of their child's inadequacies and actively sought support to help with their development. Support services that recognise low motor competence could better help mothers support their adolescent's development. One implication arising from this study is the importance of using multi-disciplinarian teams such as occupational therapist, exercise physiologist and parents to help children with low motor competence.